(untitled) (Research, Society and Development, 2023)
Objective: To analyze the experience of family members who performed a virtual visit (VV) to patients admitted to the COVID ICU at Hospital Sírio Libanês, during the pandemic. Method: Descriptive and exploratory cross-sectional study, which used a semi-structured interview designed for this purpose. The multiple-choice questions were analyzed using descriptive statistics and the open question using the Discourse of the Collective Subject (DSC) method, which works with the analysis of empirical data of a verbal nature to configure a collective subject with a social discourse. Results and discussion: The study population consisted mostly of young adults (89.47%) male (77.60%), with higher education (65.78%), connected to the city of São Paulo (63%), who had never had participated in VV (93.42%). They considered the visit time satisfactory (88.15%) and the performance extremely important (78.94%), feeling better emotionally after the performance (92.1%). The themes identified in the experience report were categorized as: alternative to the restriction of visits, fear of contamination and distance, resource for emotional coping and grief support, family participation in the care and help in the recovery of the patient, presence of anxiety due to breach of expectations about the functioning of the visit, alternative to approaching intubated patients, for farewell and guidance by psychologists providing care and reception. Conclusion: The experience with VV was considered successful, being a resource for approaching the family, which can be extended to occasions beyond the pandemic. It is suggested to expand discussions on best practices in SV, including aspects related to safety and autonomy.